STRENGTHENING THE DIMENSIONS OF PANCASILA STUDENT PROFILE IN SCHOOL MOVER IN THE ERA OF INDUSTRIAL REVOLUTION 4.0 - Astuti, Tri; Handoyo, Eko; Rosulina, Pranichayudha (UIN Sunan Kalijaga Yogyakarta, 2022)
The progressive era impacted the decline in the Pancasila values implementation in everyday life. The young generation behaves not according to the values and norms that apply in society. Based on this, it is necessary to strengthen character education in the era of the industrial revolution 4.0. In this era, science and technology developed rapidly. School mover is the school model of Kurikulum Merdeka implementation. One of the messages in the curriculum is strengthening character education. The character education implementation in the Kurikulum Merdeka is based on Pancasila values, called the Pancasila student profile. This research used qualitative methods, especially case studies. The researcher collected data by observation, in-depth interviews, and documentation; he tested the validity of the data by source triangulation and method triangulation. Data analysis included the stages of collecting data, identifying, sorting data, and concluding. Based on the research results, school movers, especially the Persatuan Umat Islam Elementary School, implemented strengthening character education by developing a religious basis, namely Islamic values. Educators trained students to implement the dimensions of the Pancasila student profile with a humanist approach and innovative strategies. They also used technology in various school activities because they educated the millennial generation; this generation is interested in technological developments.